Current Issues of Reformation of the Conceptual Categorical Apparatus of the Ukrainian Environmental Legislation - Блавацька, Д. А. (My University, 2017)
The article is devoted to the analysis of theoretical propositions for the improving «term system of national environmental legislation». The priority measures have been formulated in the context of European integration on amendments to the Law of Ukraine «On environmental protection». In particular, this Law has been supplemented by the article «Conceptual-categorical apparatus» and its compliance with the main provisions of the international standard ISO 704:2009 «Terminology work – Principles and methods». // Стаття присвячена аналізу теоретичних положень щодо вдосконалення «термінової системи національного екологічного законодавства». Пріоритетні заходи сформульовані в контексті європейської інтеграції щодо змін до Закону України «Про охорону навколишнього середовища». Зокрема, цей Закон доповнено статтею «Понятійно-категоріальний апарат» та його відповідність основним положенням міжнародного стандарту ISO 704: 2009 «Термінологічна робота - Принципи та методи».
Сучасні проблеми реформування понятійно-категоріального апарату екологічного законодавства України
Keywords: reformation of environmental legislation; the conceptual-categorical apparatus; term; category; concept; definition; term system; European integration; реформа екологічного законодавства; понятійно-категоріальний апарат; категорія; система термінів; європейська інтеграція